THE EFFECT OF COMPENSATION AND WORK MOTIVATION ON DRIVER PERFORMANCE MEDIATED BY ORGANIZATIONAL COMMITMENT - Rasminingsih, Ni Kadek Nonik; Permadi, I Komang Oka; Diputra, I Komang Suryadnya; Wardana, I Made Aditya (Graduate Program of Universitas Tarumanagara, 2023)
The demand for comfort, security, and smooth travel are just a few of the considerations that have made transportation so important in today's Indonesia. This study aims to evaluate and confirm the relationship between pay, workplace motivation, and organizational commitment to driver performance. 1090 drivers make up the study's population. 235 drivers will be included in the sample for this study, which will be selected using a proportionate random sampling. The application of SmartPLS version 3.2.9 is utilized to test the data gathered in this study, and path analysis is employed to test hypotheses in the research. The results showed that the driver's performance was significantly influenced by pay, motivation, and organizational commitment. Compensation and work motivation have a significant impact on organizational commitment. Driver performance can be influenced by compensation and work motivation, although organizational commitment can moderate this effect.